KONTRIBUSI HAKIM PEREMPUAN DALAM PENEGAKAN HUKUM DI INDONESIA - Djazimah Muqoddas (Asy-Syari'ah, 2016)
This article describes the contribution of female judges in law enforcement in Indonesia through the approach of a critical study of the Koran interpretation letter al-Nisâ’ verse 34 and an explanation of the hadiths of the Prophet Muhammad SAW who describes the position of women as judges in the judiciary. So this article will be focused on: (1) polemic female judges in religious courts; (2) female judges in the legal system in Indonesia; and (3) the position of women judges in Islamic legal system. From this discussion, the female judge is required to give good imaging as judges always give a good example to the parties and to other law enforcement officials, as long as he completed cases in the judicial sphere. However, imaging judge women as law enforcement officials so bound by a code of conduct (ethical code) and the oath of their profession.